الصداع التالي للتخدير القطني عند القيصريات دراسة مقارنة بين إبر البزل القطني G25- G27 - إبراهيم, رزق الله; الدالي, عصام; حاتم, ربى (Latakia University Journal -Medical Sciences Series, 2019)
يعتبر الصداع التالي لبزل الأم الجافية مشكلة هامة تعرقل تطبيق هذا النوع من التخدير وخاصة عند النساء الولودات بطريقة القيصرية. وتختلف نسبة حدوث الصداع حسب الدراسات فهي تتراوح بشكل تقريبي ما بين (20-30%) وهي نسبة ليست قليلة مما دعانا لإجراء دراسة للصداع التالي للتخدير القطني. أجريت دراستنا في مشفى الأسد الجامعي في اللاذقية في قسم التخدير والإنعاش بالتعاون مع قسم التوليد وأمراض النساء خلال العام 2004- 2005 وتضمنت دراستنا مئة قيصرية تراوحت أعمارهن بين 15-45 سنة قسمت المريضات بشكل عشوائي إلى مجموعتين: في المجموعة الأولى تم استعمال إبر بزل قطني ذات قياس G25 وفي المجموعة الثانية تم استعمال إبر بزل قطني ذات قياس G27 ولقد صادفنا عشر حالات صداع: تسع حالات في المجموعة الأولى (18%) وحالة واحدة في المجموعة الثانية (2%). توزعت عدد حالات الصداع حسب شدته في المجموعة الأولى ثلاث حالات صداع خفيف, أربع حالات صداع متوسط, حالتان صداع شديد بنسب مئوية: 6%, 4%, 8% على التوالي. توزعت عدد حالات الصداع حسب شدته في المجموعة الثانية: حالة صداع خفيف, حالة واحدة صداع متوسط, حالة صداع شديد بنسب مئوية 0%, 2%, 0%, على التوالي. من هنا نجد أن النسب تختلف كثيراً حسب حجم الإبر المستعملة أي إن استخدام الإبر الرفيعة جداً وذات القطر الصغير سيخفف نسبة وشدة الصداع التالي للتخدير القطني. كانت النسبة المئوية للصداع في النسبة المئوية للصداع في المجموعة الأولى بعد محاولة بزل وحيدة 12.82% وبعد عدة محاولات 36.36% في حين أن النسبة المئوية للصداع في المجموعة الثانية بعد محاولة بزل وحيدة 0% وبعد عدة محاولات 5%. أي إن نسبة الصداع زادت في المجموعتين عند إجراء عدة محاولات لبزل الجافية. لذلك يجب دوماً محاولة إجراء بزل الجافية من المرة الأولى. قسمت المريضات حسب كمية السوائل المسربة وريدياً إلى فئتين: فئة آ: تم تسريب (300-200) مل قبل التخدير. فئة ب: تم تسريب (1000-600) مل قبل التخدير. حدث الصداع بنسبة 15% في كل فئة أي إن نسبة الصداع لم يكن لها علاقة بكمية السوائل المسربة وريدياً قبل البزل القطني ولكن يجب إعطاء السوائل بكمية كافية قبل البزل القطني لتجنب هبوط الضغط الشرياني. معظم المريضات كن راضيات عن التخدير القطني كما أن المريضات اللواتي عانين من الصداع لم يربطنه مع هذا النوع من التخدير. Considered an important problem, therefore, the application of this type of spinal anesthesia is not preferred. The incidence of headache differs according to the studies. It is average (20.30) %. The incidence is not low, therefore we studied Post- spinal headache. Our study was carried out in the Anesthesia and in collaboration Reanimation Department We divided the patients into group. We used puncture needles G25 in group 1, and we used puncture needles G27 in group 2. We saw (10) headaches cases.(9)case in group l (18) %, (1) case in group2(2) %.By comparison between two groups, we found that the rate of headache differs according to the size of puncture needles. Therefore we must use the smallest size of puncture needles. The number of headache divided according to severity: 3 patients in group one had mild headache (6%). 4 patients had moderate headache (8%). 2 patients had severe headache (4%). In group 2 we found: No patient had mild headache (0%). 1 patient had moderate headache (2%). No patient had severe headache (0%). By comparison we concluded that the rate of headache differs very much according to the size of puncture needles, therefore when we used the smallest puncture needles the rate & severity of PHPD will decrease. In group 1, the percent of headache after one attempt to dural puncture was 12.82% & after several attempts was 36.36%. In group 2, the percent of headache after one attempt to dural puncture was 0% & after several attempts was 5%. We concluded that the percent of headache increased very much in the two groups when we punctured the dural several times, therefore we must puncture dural from the first attempt. We divided the patients according to the amount of intravenous liquids before spinal anesthesia into parts: Part 1 we provided the patients with (200 - 300) ml before anesthesia. Part 2 we provided the patients with (600 -1000) ml before anesthesia. We founded that the rate of the headache was independent of the amount of intravenous liquids before spinal anesthesia. Most patients satisfied with spinal anesthesia.